A Nonlinear Dynamical System Perspective on Team Learning: The Role of Team Culture and Social Cohesion - Dimas, Isabel (2019)
This paper examines team learning within a nonlinear dynamical system (NDS) perspective. Research has successfully identified various conditions that promote learning behaviors in teams. In the present study, our focus is on the role played by team culture and by social cohesion as supporting conditions of team learning. Previous studies revealed that a culture oriented to learning tends to promote the adoption of team learning behaviors in the group. Results concerning the role played by social cohesion in team learning is, however, less clear. Indeed, while social cohesion might promote learning behaviors because it increases the willingness to work together and to help each other, high levels of social cohesion could also lead to uncritical acceptance of solutions. The complex relationship between social cohesion and team learning behaviors led us to study it under the NDS framework. Using the dynamic difference equation model, the present research proposes a cusp catastrophe model for explaining team learning, implementing the team culture as the asymmetry variable and social cohesion as bifurcation variable. The sample of the present research is constituted by 44 project workgroups, and data were collected at two moments of the life cycle (half-time and end) of teams, with single-item visual analogue scales. Results reveal that the cusp models are superior to the pre-post linear models by explaining a larger portion of the variance. In addition, the cubic term, the bifurcation effect and the asymmetry term are statistically significant. Social cohesion acts as a bifurcation factor, that is to say, beyond a certain threshold of social cohesion, groups that have the same cultural orientation might oscillate between two attractors, the modes of high and low learning behaviors respectively. These results suggest that a small variation of social cohesion causes the system to enter an area of unpredictability in terms of team learning, where sudden shifts in the outcomes might be expected. Leaders and members need to monitor the levels of social cohesion of the team, to avoid phenomena like groupthink, which jeopardizes the implementation of learning behaviors, such as the exploration of different opinions or error discussion.